Transition metal-free coupling reactions of benzylic trimethylammonium salts with di(hetero)aryl disulfides and diselenides. Issue 85 (1st October 2020) - Li, Fuhai; Wang, Dan; Chen, Hongyi; He, Ze; Zhou, Lihong; Zeng, Qingle
Abstract : Benzylic thioethers and selenoethers with high enantiopurity and yield were synthesized via transition-metal-free coupling reactions of benzylic trimethylammonium salts. Abstract : A new protocol was developed to synthesize (enantioenriched) thioethers and selenoethers from (chiral) benzylic trimethylammonium salts and di(hetero)aryl disulfides or diselenides. These syntheses were promoted by the presence of weak base and did not require the use of any transition metal, and resulted in the target products with good to excellent yields (72–94%). Using quaternary ammonium salts synthesized from enantiomerically enriched amines led to highly enantiopure benzylic thioethers and selenoethers (94–99% ee) with configurations reversed from those of their enantioenriched quaternary ammonium salts.